Let’s Play! Digital and Analog Play Patterns between Preschoolers and Parents - Hiniker, Alexis; Lee, Bongshin; Kientz, Julie A.; Radesky, Jenny S. (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
Play is an enjoyable and developmentally useful part of early childhood, and parent-child play is a highly productive mechanism by which children learn to participate in the world. We conducted an observational lab study to examine how 15 parent-child pairs (children age 4-6) respond to and play with tablet apps as compared to analog toys. We found that parents and children were less likely to engage with each other or to respond to each other’s bids for attention during play sessions with tablets versus play sessions with toys. We also observed that specific design features of tablet devices and children’s apps—such as one-sided interfaces, game paradigms that demand continual attention, and lack of support for parallel interaction—are the primary mechanism shaping these differences. We provide guidance suggesting how children’s apps might be re-designed to preserve the advantages of digital play experiences while also evolving to build in the advantages of traditional toys.